2011
DOI: 10.1002/chem.201002538
|View full text |Cite
|
Sign up to set email alerts
|

N‐Heterocyclic Carbene‐Catalyzed Michael Additions of 1,3‐Dicarbonyl Compounds

Abstract: A study of the organocatalytic activity of N-heterocyclic carbenes (NHCs) in the Michael addition of 1,3-dicarbonyl compounds has allowed us to identify 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene (IPr) as an excellent catalyst for this transformation (up to 99 % yield with a 2.5 mol % catalyst loading), and the reaction was found to be of broad scope. Two early applications of this unprecedented catalytic activity of NHCs are described, that is, the domino carbocyclization reactions of simple cyclic 1,3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 52 publications
1
22
2
1
Order By: Relevance
“…Confirming our initial hypothesis, we found that strong Brønsted base NHCs, such as N,N-dialkylimidazolium-generated NHCs, neither catalysed nor generated appreciable conversion for this reaction. This result is in sharp contrast to previous reports that used NHCs as Brønsted bases for both oxy-and carbo-Micheal addition reactions 45,46 . Those reports primarily used N-alkyl imidazolium-derived NHCs because they are strongly basic.…”
Section: Analysis Of Nhc-catalysed Michael Addition Reactionscontrasting
confidence: 99%
See 1 more Smart Citation
“…Confirming our initial hypothesis, we found that strong Brønsted base NHCs, such as N,N-dialkylimidazolium-generated NHCs, neither catalysed nor generated appreciable conversion for this reaction. This result is in sharp contrast to previous reports that used NHCs as Brønsted bases for both oxy-and carbo-Micheal addition reactions 45,46 . Those reports primarily used N-alkyl imidazolium-derived NHCs because they are strongly basic.…”
Section: Analysis Of Nhc-catalysed Michael Addition Reactionscontrasting
confidence: 99%
“…However, an attempt to influence this reaction asymmetrically was unsuccessful, likely due to the two aforementioned reasons (Fig. 2c) 46 . In our opinion, these fundamental obstacles have prevented the development of successful asymmetric Brønsted base catalysis using NHCs.…”
Section: Analysis Of Nhc-catalysed Michael Addition Reactionsmentioning
confidence: 99%
“…The same group also demonstrated the intermolecular coupling of 1,3-dicarbonyls with vinyl electron-withdrawing groups. 280 Recently, Chen and Huang demonstrated the stereoselective 1,4-addition of 1,3-dicarbonyl compounds to nitrostyrene derivatives. 281 Mechanistically, the reaction is believed to proceed via complexation between the free carbene and the cyclic enol form of the 1,3-dicarbonyl 266 , activating it.…”
Section: Lewis Base Catalysismentioning
confidence: 99%
“…The first intermediate 15 , obtained after trapping the α‐oxo‐ketene,67 is engaged in a microwave‐assisted olefin cross‐metathesis68 with acrylic derivatives using precatalyst 16 , to furnish the key conjugated olefin 19 . Finally, upon addition of a catalytic amount of N,N ‐diaryl‐1,3‐imidazol(in)‐2‐ylidenes NHCs 18 , the intramolecular Michael spiroannulation to 17 occurs readily at room temperature 69. Overall, the described consecutive reaction has allowed the preparation of the target α‐spiro compounds using only a single equivalent of each of the three reaction partners and a catalytic amount of additives with a rapid increase in molecular complexity.…”
Section: Mbfts With Four Bond‐forming Eventsmentioning
confidence: 98%